In Hades of Homer and Hesiod: Death and Human’s Fate after Death in the People’s Beliefs of Archaic Greek Culture - Baran, Grzegorz M. (Roczniki Kulturoznawcze, 2010)
The works of Homer and Hesiod, expressing people’s mentality of the archaic Greek culture, supply inter alia much information about people’s beliefs of that period concerning death and posthumous fate of humans. In the light analysis, one can notice that the people of that time period (being based on quotidian experience) had no doubts that humans were mortal beings. Although death inspired horror among the living the Greeks did not it amounted to total annihilation of man. They believed the spiritual part of human – ψυχή (psyché) survived mortal death leaving the body to go to the land of the dead. This place was known as Hades somewhere both far and deeply in relation to inhabited by people earth. The soul that exists in Hades, leads a generally gloomy and rather sad life. However, their posthumous fate, apart from few exceptions of the rebels against divine commandments – can’t be perceived as punishment, because in considered by people of today because people of that time had no concept of the Last Judgement and retribution after death.